De caja real a hacienda provincial. Cambios y continuidades en la jurisdicción fiscal de Santa Fe (Río de la Plata) entre 1805 y 1815 - Galarza, Antonio (Anuario de Historia de América Latina, 2020)
This article reconstructs the tax structure of Santa Fe province between the last years of colonial regime and the first years of independence seeking to identify changes and continuities in the performance of regional taxation. The paper examines the evolution of income and expenses and identifies the changes in the collection of the main taxes taking into account the modifications suffered by the most relevant expenses, classified according to their allocation (military, frontier, administration). It analyzes the fiscal pressure imposed by the regional treasury and its internal connections as well as those to other fiscal jurisdictions, such as the municipal (Cabildo of the city of Santa Fe) and the central administration of the Buenos Aires treasury, before and after 1810. For the reconstruction of the accounts of incomes and expenses the article relies on the general ledgers and accounting manuals.